PENEGAKAN HUKUM SEBAGAI SALAH SATU FAKTOR UTAMA KEBERHASILAN TATA KELOLA PEMERINTAHAN JOKOWI-RUDY DI KOTA SURAKARTA - Teguh Yuwono (Faculty of Law, Universitas Diponegoro, 2014)
Law enforcement is one important thing in achieving local good governance in Surakarta City under Jokowi-Rudy. The main question of this research is how comes law enforcement contributes to the success of local good governance in Surakarta. Qualitative method is used in answering the researh questions. Research results show that rule law is one pivotal factor in good local governance of Surakarta. The method of rule of law in Surakarta City is uniqe since it uses humanistic approach in enforcing the laws. This approach is effective since conducive supports from civil society